Χρήση τεχνικών Design of Experiments (D.O.E) στη διαδικασία επεξεργασίας οργανικών φωτοβολταϊκών με στόχο την βελτιστοποίηση της απόδοσης - Χατζηπαπά, Άντρη (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
In the beginning of this project work, a study was made on different structures of Organic Photovoltaics (OPV) cells (single layer, bi-layer, bulk heterojunction). Next, the various processes and experimental equipments used for the deposition of various layers of an OPV cell were examined. A study on the Design of Experiments (DOE) methods and their fields of application was also made. After the above, it was decided to apply a Taguchi method on an OPV cell with a bulk heterojunction structure, with focus to the inkjet printing of PEDOT/PSS on glass substrate. The final target is to achieve a good quality of printed surface with the less possible experiments. Due to several malfunction during the printing process, the PEDOT/PSS was substituted by Copper (Cu). Taguchi method of orthogonal arrays (L9) was applied twice (a total of 18 experiments) by using Copper as the inkjet printing material but without reaching, at the end, a printed surface with the desirable quality. The above results have not allowed the application of further steps in the Taguchi method. The final conclusion of this project work is that the deposition of Copper on a glass substrate by the use of the inkjet printing method, as part of the development of an OPV device should be further examined. Although it was not able to achieve a surface of accepted quality, results have shown that Copper has the potential to reach this target. Further research work in modifying existing experimental parameters or adding new ones is recommended.
Keywords: Taguchi Μethod; Organic Photovoltaics; Copper; Φωτοβολταϊκά; Μέθοδος Taguchi; Χαλκός